Aayabya Kyap: The Symbolic Heart of Khaling Rai Marriage and Kinship - Rai, Bina Khaling Rai (Journal of Nepalese Studies, 2025)
This article examines marriage among the Khaling Rai as a central cultural institution that sustains kinship relations, shared identity, and moral values. It argues that marriage in Khaling society is not merely a union between two individuals but a culturally meaningful process embedded in lineage continuity, ritual obligations, and symbolic practices. Particular attention is given to Aayabya Kyap (copper pots), ritual objects whose symbolic significance is grounded in tamra (copper) ideology. Drawing on ethnographic fieldwork conducted in Mapyadudhakoshi Gaupalika–3, Solukhumbu District, eastern Nepal, the study employs participant observation, conversations with Khaling ritual specialists, and documentation of marriage ceremonies. Employing a symbolic anthropological framework, the article interprets ritual actions and objects as expressions of deeper cultural meanings. The findings demonstrate that Aayabya Kyap function as key symbolic mediators in Khaling marriage rituals, shaping kinship relations, legitimizing affinal ties, and reinforcing the moral and social order of Khaling Rai society. Overall, the study highlights how Khaling marriage rituals continue to serve as vital cultural spaces for maintaining and renewing collective identity and social solidarity.